Modeling leaflet correction techniques in aortic valve repair: A finite element study - Labrosse, Michel; Boodhwani, Munir; Sohmer, Benjamin; Beller, Carsten J. (Journal of biomechanics, 2011)
In aortic valve sparing surgery, cusp prolapse is a common cause of residual aortic insufficiency. To correct cusp pathology, native leaflets of the valve frequently require adjustment which can be performed using a variety of described correction techniques, such as central or commissural plication, or resuspension of the leaflet free margin. The practical question then arises of determining which surgical technique provides the best valve performance with the most physiologic coaptation. To answer this question, we created a new finite element model with the ability to simulate physiologic function in normal valves, and aortic insufficiency due to leaflet prolapse in asymmetric, diseased or sub-optimally repaired valves. The existing leaflet correction techniques were simulated in a controlled situation, and the performance of the repaired valve was quantified in terms of maximum leaflets stress, valve orifice area, valve opening and closing characteristics as well as total coaptation area in diastole. On the one hand, the existing leaflet correction techniques were shown not to adversely affect the dynamic properties of the repaired valves. On the other hand, leaflet resuspension appeared as the best technique compared to central or commissural leaflet plication. It was the only method able to achieve symmetric competence and fix an individual leaflet prolapse while simultaneously restoring normal values for mechanical stress, valve orifice area and coaptation area.
Gesehen am 12.07.2022